Comparative analysis of extracellular vesicles from induced and adipose-derived Mesenchymal Stem Cells: Implications for regenerative medicine - Sura Nashwan; Mohammad A. Ismail; Tareq Saleh; Sabal Al Hadidi; Enas Alwohoush; Momen Sarhan; Nizar Abu Harfeil; Abdalla Awidi; Nidaa A. Ababneh (PLoS ONE, 2025)
Extracellular vesicles (EVs), which include exosomes (Exos) and microvesicles (MVs), play a crucial role in intercellular communication and exert various biological activities by delivering specific cargoes of functional molecules, such as RNAs and proteins, to target cells. EVs secreted by human mesenchymal stem cells (hMSCs) have demonstrated their capacity to replace intact MSCs in tissue repair and regeneration. Induced mesenchymal stem cells (iMSCs) derived from induced pluripotent stem cells (iPSCs) present a promising alternative to traditional MSCs for producing EVs. This study aimed to establish an alternative source of EVs from iMSCs and compare them with EVs from adipose-derived MSCs (ADMSCs). Both iMSCs and ADMSCs were expanded under xeno-free culture conditions, and conditioned media were collected for EV isolation and characterization. The effects of the isolated EVs on cellular viability, apoptosis, senescence, and cell migration were evaluated. Results indicated that iMSC-EVs had a larger particle size (~1.5-fold) with no significant differences in morphology or surface markers compared to ADMSC-EVs. Furthermore, both iMSC- and ADMSC-derived EVs significantly increased HDF viability at 48 and 72 hours (p ≤ 0.01, p ≤ 0.05). Both types of EVs significantly reduced apoptosis levels (p ≤ 0.01) in both HDFs and ADMSCs, while having no effect on senescence induction (p > 0.9999). Additionally, iMSC-EVs significantly enhanced ADMSC migration (p < 0.0001), whereas the effect was less pronounced with ADMSC-EVs. iMSC-EVs present a promising and a scalable option for regenerative applications, offering advantages over ADMSC-EVs. However, further investigation is needed to fully understand their effects and underlying mechanisms.